Iron deficiency in endure athletes - Rogulski, Michał; Patarocha, Yauheniya; Ślusarska, Aleksandra; Mędyk, Jolanta; Błasiak, Paulina; Wirkijowska, Małgorzata; Mikołajec, Patryk; Huk, Ruslan; Bilecka, Barbara; Wirkijowski, Jakub (Quality in Sport, 2025)
Iron deficiency, with or without anemia, is more prevalent in endurance athletes than in the general population. Especially in marathon and half-marathon runners - these groups of endurance athletes are at high risk for iron deficiency via several mechanisms, such as sweating, gastrointestinal bleeding, urinary-tract blood loss, hemolysis, and others. Methods: Our study followed the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [9]. A literature search was conducted using the online electronic databases such as PubMed and ScienceDirect. Keywords which were searched for in this study: “Hemoglobin”, “Iron”, “Iron Deficiencies”, “Hepcidin”, “Ferritin”, Transferrin”, “Hemoglobin”, “Athletes” and “Athletic performance”. This search included human and experimental studies. Randomized controlled trials (RCTs) were included as well. We prioritized articles published within the last 10 years; however, to assert more relevant information, the earlier articles were also included in our study. We eliminated duplicate articles, articles not in English, and not relevant for our research articles (for example, the RCTs in non-athletes or RCTs which don't reflect the correlation between iron status and sport performance). Summary information from these articles was synthesized together to create a narrative review of the literature. Results: the correlation between physical performance in endurance athletes and their iron status turned out to be significant. Athlete's physical performance can be improved by improving their iron status. Our review revealed that iron supplementation has the most pronounced effect on physical performance in athletes, especially in those with lower ferritin levels. Conclusions: Iron is playing a key role in numerous metabolic functions of the human body. The disruption of the balance of iron leads to decreased athletic performance. Iron deficiency has been widely described in many studies regarding athletes, especially in endurance ones. Intense exercise leads to iron deficiency due to foot strike hemolysis, iron loss in sweat, gastrointestinal bleeding, urinary-tract blood loss and decreased iron absorption. To prevent iron deficiency it is extremely important to introduce iron-rich foods to your diet. Iron-rich foods (such as meat, poultry, and seafood) contain the heme form, which has superior bioavailability compared to non-heme form contained mostly in plant-based foods. Therefore, athletes from a high-risk group of iron deficiency as vegans, vegetarians, and those who resign from meat because of personal, health or religion, should pay more attention to their dietary iron intake and may require additional supplementation of iron (oral, intramuscular or intravenous). Also, special attention should be paid to female athletes, who are in high-risk of iron deficiency due to heavy menstrual bleeding. Moreover, to avoid the inhibition of iron absorption from the gastrointestinal tract it is recommended to reduce the consumption of such products as tea, coffee, and milk, at least one hour before and after iron supplementation.